Pain Management in Special Circumstances - Shallik, Nabil A. (IntechOpen, 2018)
Like management of disease, management of pain is as old as the human race. When patients come to us with their pain, they present us with a wonderful opportunity: the chance to understand them, to understand how their pain is affecting their lives, the challenge of discovering what is causing their pain, and finally the opportunity to prescribe medications and lifestyle changes to help them gain relief from their pain. It is hoped that this book will provide the latest evidence-based updates on pain management in special circumstances and will serve as a ready reference for those embarking on pain management. Its intent is not to be a heavy book that can only be stored on a bookshelf, but a pocket-sized reference that can be carried, be easily navigated, and be available whenever a conceptual gap compromises pain physicians and their ability to treat their patients.